2013
DOI: 10.1002/stem.1315
|View full text |Cite
|
Sign up to set email alerts
|

An Oct4-pRb Axis, Controlled by MiR-335, Integrates Stem Cell Self-Renewal and Cell Cycle Control

Abstract: The pluripotency of mouse embryonic stem cells (mESCs) is controlled by a network of transcription factors, miRNAs, and signaling pathways. Here, we present a new regulatory circuit that connects miR-335, Oct4, and the Retinoblastoma pathway to control mESC self-renewal and differentiation. Oct4 drives the expression of Nipp1 and Ccnf that inhibit the activity of the protein phosphatase 1 (PP1) complex to establish hyperphosphorylation of the retinoblastoma protein 1 (pRb) as a hallmark feature of self-renewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 34 publications
4
39
0
Order By: Relevance
“…Such a defect in self-renewal can be rescued by ectopic expression of a Tex10 transgene that lacks the shRNA target site, excluding off-target effects of the shRNAs (Figures S2B–C). Of note, a similar requirement of the core pluripotency factors OSN for efficient G1/S transition in both human (Card et al, 2008; Zhang et al, 2009) and mouse (Schoeftner et al, 2013) ESCs has also been reported, suggesting a potential functional interaction between Tex10 and OSN.…”
Section: Resultsmentioning
confidence: 57%
“…Such a defect in self-renewal can be rescued by ectopic expression of a Tex10 transgene that lacks the shRNA target site, excluding off-target effects of the shRNAs (Figures S2B–C). Of note, a similar requirement of the core pluripotency factors OSN for efficient G1/S transition in both human (Card et al, 2008; Zhang et al, 2009) and mouse (Schoeftner et al, 2013) ESCs has also been reported, suggesting a potential functional interaction between Tex10 and OSN.…”
Section: Resultsmentioning
confidence: 57%
“…Conversely, other studies had found that a delay in G1-S phase transition in human ESCs (hESCs) could up-regulate dephosphorylated pRb and induce the loss of Oct-4 (Filipczyk et al, 2007). In addition, some studies confirmed that high Oct4 expression increased the inhibitors of the major pRb phosphatase to maintain the hyperphosphorylation of pRb, which influenced the maintenance of stemness and the cell cycle control of stem cells (Schoeftner et al, 2013). Here, we determined that prolonged anesthesia with dexmedetomidine or fentanyl caused rising cell numbers in the G1 phase and down-regulation of Oct4 and Sox2 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of checkpoint control is required for cancer initiation and development (43,44). Thus, there is a clear direct connection between miRNAs and cancer formation, which will not be discussed further in the present review.…”
Section: Signalling Cascades With Microrna Interactionmentioning
confidence: 95%
“…Lynch et al (42) reported that miR-335 was able to suppress metastasis of neuroblastoma cells by directly repressing the downstream effector proteins of the transforming growth factor (TGF)-β pathway, namely Rho-associated, coiled-coil containing protein kinase 1 (ROCK1) and mitogen-activated protein kinase 1 (MAPK1), which consequently reduced the phosphorylation levels of myosin light chain and inhibited the invasiveness of neuroblastoma cells. In addition to its regulatory function in signaling pathways, miR-335 has roles in at least two pathways involved in cell cycle control, namely ataxia telangiectasia mutated (ATM)-dependent DNA damage control (43) and octamer-binding transcription factor 4-retinoblastoma protein (Oct4-pRB)-dependent stem cell renewal/cell cycle control (44). In the ATM pathway, irradiation-activated ATM downregulates miR-335 via cyclic adenosine monophosphate response element binding protein, which subsequently activates C terminal binding protein interaction protein, which in turn recruits breast cancer 1, early onset to double strand breaks (43).…”
Section: Mir-21 In Cd133mentioning
confidence: 99%
See 1 more Smart Citation